Pengaruh Perceraian pada Pasangan yang Menikah karena Kehamilan di Luar Nikah Menurut Hukum Islam - Olis Wulandari; Alvin Nurrizky Ahmad; Ahmad Adam Baihaqi Bahren; Sunengsih; Fatih Musthofa; Thoriq Jiyadi; Hapizul Ahdi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Divorce among couples who marry due to pregnancy outside of marriage presents complex legal and social challenges within the framework of Islamic family law. Such marriages are often conducted under social pressure and limited preparedness, increasing vulnerability to marital breakdown. This article examines the legal position of marriage involving pregnant women outside wedlock, the factors contributing to divorce in such unions, and the legal consequences for spouses and children from the perspective of Islamic law and positive law in Indonesia. Employing a normative juridical method with a descriptive-analytical approach, the discussion is based on statutory regulations, classical fiqh doctrines, the Compilation of Islamic Law, and relevant scholarly literature. The analysis indicates that external pressures, weak mental readiness, and unfavorable social environments are dominant factors leading to divorce in these marriages. Islamic law permits marriage with a pregnant woman under specific conditions and emphasizes the protection of children’s rights as a moral and legal obligation. Nevertheless, the status of lineage and civil rights of children born outside lawful marriage remains limited to the maternal line unless supported by legal proof. The findings highlight that Islamic law seeks to balance legal certainty, moral responsibility, and child protection, ensuring that divorce does not eliminate parental obligations toward the welfare of children.